Shortened Positive and Negative Symptom Scale as an Alternate Clinical Endpoint for Acute Schizophrenia Trials: Analysis from the US Food & Drug Administration. Issue 1 (6th November 2020) - Gopalakrishnan, Mathangi; Farchione, Tiffany; Mathis, Mitchell; Zhu, Hao; Mehta, Mehul; Uppoor, Ramana; Younis, Islam
Abstract : Objective: To evaluate the performance of the individual Positive and Negative Symptom Scale (PANSS) items, and to assess the feasibility of using a shortened version of the PANSS as an alternative regulatory endpoint for evaluating the efficacy of drugs to treat schizophrenia. Design: Data from 32 randomized, placebo‐controlled, multiregional trials from eight atypical antipsychotic programs (N=14, 219) submitted to the US Food and Drug Administration were used in the analyses. Item response theory analysis on baseline PANSS item scores was used to identify the best performing items of the PANSS to derive the shortened, or modified, PANSS (mPANSS). Concordance rates of mPANSS total with the PANSS total trial results at week 6 were examined, and implications of using mPANSS on trial sample size evaluated. Results: Five of the positive items, six of the negative items, and eight of the general items were assessed as sensitive to describe the underlying symptom severity and comprise mPANSS. The overall concordance rate between mPANSS and total PANSS results at week 6 was 97.6%. Using mPANSS resulted in a 32% reduction in samples size relative to using total PANSS. Conclusions: Based on this research, mPANSS may be considered a potential alternative clinical endpoint for acute schizophrenia trials. However, it will need psychometric validation before it can be fully implemented in clinical trials in place of total PANSS. If such implementation occurs, the development of new drugs for schizophrenia, a public health imperative, may be considerably improved. HIGHLIGHTS: The current research is a comprehensive analysis of one of the largest database of randomized, placebo‐controlled trials for drugs indicated for schizophrenia to evaluate the feasibility of a shortened version of PANSS (mPANSS) as a regulatory clinical endpoint. The mPANSS consisting of 19 out of 30 PANSS items was identified to be sensitive to assess the schizophrenia symptom severity by item response analysis. Based on this research, mPANSS may be considered a potential alternative clinical endpoint for acute schizophrenia trials.